Unblocking the flow of biodiversity data for decision-making in Africa. (September 2017) - Stephenson, P.J.; Bowles-Newark, Nadine; Regan, Eugenie; Stanwell-Smith, Damon; Diagana, Mallé; Höft, Robert; Abarchi, Harouna; Abrahamse, Tanya; Akello, Christine; Allison, Hilary; Banki, Olaf; Batieno, Barthelemy; et al.
Abstract: African countries need to conserve biodiversity and use natural resources rationally if they are to avoid continued environmental degradation that jeopardizes sustainable development and human wellbeing. However, many government agencies cannot access or use the biodiversity data they need to make informed decisions for environmental and economic management. More than forty stakeholders representing governments, civil society organizations (CSOs) and UN agencies, including delegates from 20 African states, identified decisions that require biodiversity information and explored blockages and potential solutions to data access and use. The participants concluded that the key enabling environment includes data availability, data quality and usability, willingness to collect and use data, and financial and technical capacity. We recommend that African government departments across sectors work with academic bodies and CSOs to: i) enhance internal resources for monitoring and develop partnerships with donors; ii) build capacity for data collection, using tools, guidelines and communities surrounding CBD planning and biodiversity monitoring; iii) improve national and international co-ordination and cross-sectoral collaboration for biodiversity data management; iv) produce and use more data-derived products that encourage data use, especially assessments that demonstrate the importance of biodiversity to economies and wellbeing and dashboards that facilitate interpretation and analysis. Governments, CSOs and academic bodies should test different science-policy interfaces in a handful of pilot countries or regions, building on existing models to demonstrate how data providers and users can work together to break down barriers to data access and sharing and mainstream biodiversity information into decision-making. Highlights: Decision makers are not adequately using biodiversity data in Africa. Data availability, quality and usability enable use. Capacity and willingness to use data are also vital. Improving co-ordination and cross-sectoral collaboration will help. Science-policy interfaces to enhance data use need to be tested.